Reframing Education for Multilinguals: Honoring Students’ Linguistic, Literacy, and Cultural Assets - Abugasea Heidt, Marium; Svrcek, Natalie Sue (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2025)
Multilingual students enter classrooms with complex language, literacy, and cultural repertoires. Drawing on these repertoires, they use knowledge, skills, practices, and perspectives that make their language and literacy practices dynamic. This paper, based on a context review of educational policies and practices in the United States, as well as a literature review of transformative pedagogies, asserts the importance for teachers to honor and empower students’ use of dynamic practices to make and share meaning. To this end, and in order to help reframe education for multilinguals, in this paper we provide strategies to help foster students’ multilingualism, multiliteracies, and multiculturalism.